Penegakan Hukum terhadap Tindak Pidana Penipuan Berbasis Media Sosial di Indonesia : Studi tentang Maraknya Kasus Penipuan di Masyarakat - Ayu Triningsih; Lusiana Margareth Tijow; Nugraha Ardi Setiawan; Ajeng Laksmi Ambarwati; Fannisa Mawarnina Adwisti; Fitri Elia; Lu'luun Nisaul Mukaromah; Nabila Nur Ramadhani; Nadine Aulia Putri; Nina Sofiana Santoso; Sasmita Rosmila; Zidan Kilmi Nasrullah (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This study aims to analyze law enforcement against social media–based fraud in Indonesia through a normative and empirical juridical approach. The focus is directed at the application of Article 378 of the Criminal Code and Article 28 paragraph (1) in conjunction with Article 45A paragraph (1) of the ITE Law, which often create challenges in practice, particularly in proving the elements of fraud and the dissemination of misleading information. The results indicate overlapping regulations, difficulties in digital evidence and inconsistencies in enforcement by law officers. Empirically, these issues contribute to the low effectiveness in handling such cases. Therefore, clearer legal norms, technical guidelines for digital evidence and strengthening the capacity of law enforcement agencies are necessary.